Effects of classroom‐based active breaks on cognition, sitting and on‐task behaviour in children with intellectual disability: a pilot study. Issue 5 (15th March 2021) - Mazzoli, E.; Salmon, J.; Pesce, C.; Teo, W.‐P.; Rinehart, N.; May, T.; Barnett, L. M.
Abstract: Background: Classroom‐based active breaks can help typically developing children reduce sitting, increase physical activity and improve cognitive functions and on‐task behaviour. Yet, this strategy has not been tested in children with intellectual disability (ID) – a population who are insufficiently active. This study aimed to investigate the effects of a 5‐week active breaks intervention on cognitive functions and on‐task behaviour in schoolchildren with ID. Methods: Twenty‐four children, aged between 8 and 12 years (37.5% girls), were recruited. Children's cognitive functions (response inhibition, lapses of attention, interference and working memory) were measured at baseline and end of trial using computer‐based tests. Sitting, standing and movement patterns were assessed with inclinometers, and on‐task behaviour was directly observed in the classroom before and after active breaks, at baseline, mid‐trial and end of trial. Linear mixed models were used to investigate the intervention effects on cognitive functions and sedentary patterns; generalised linear mixed models were used to analyse on‐task behaviour data. Results: A significant time × group interaction was found for working memory favouring the intervention ( B  = 11.56, 95% confidence interval [1.92, 21.21]). No significant effects were found in relation to the other measures of children's cognition or on‐task behaviour. Stepping time and bouts of sitting were positively affected. Conclusions: Classroom‐based active breaks can increase physical activity and reduce sedentary behaviour in children with ID and might also benefit their working memory. Further research is required to clarify the effects on cognition and to investigate whether this strategy has other benefits in this population.